Association Between Metformin and Abdominal Aortic Aneurysm: A Meta-Analysis - Niu, Wenqiang; Shao, Juan; Yu, Benxiang; Liu, Guolong; Wang, Ran; Dong, Hengyang; Che, Haijie; Li, Lubin (Frontiers in Cardiovascular Medicine, 2022)
Objective To systematically examine the association between metformin and abdominal aortic aneurysm (AAA) and provide a basis for the treatment of AAA. Methods Pubmed, Embase, Cochrane Library, and Ovid databases were searched by computer to identify the literature related to metformin and AAA published until February 2022. The literature was screened according to the inclusion and exclusion criteria, data were extracted, and a quality assessment was conducted. The meta-analysis was performed using Stata 16.0 and RevMan 5.3 software. Results Seven articles containing a total of 10 cohort studies (85,050 patients) met the inclusion criteria and were included in the review. Meta-analysis showed that metformin can limit the expansion of AAA (MD = – 0.72, 95% CI: – 1.08 −0.37, P < 0.00001), as well as reduce AAA repair or AAA rupture-related mortality (OR = 0.80, 95% CI:0.66 0.96, P = 0.02). The difference was statistically significant (P < 0.05). Conclusion Metformin can limit the expansion of AAA and reduce the incidence of AAA and postoperative mortality. However, further biological experiments and clinical trials still need to be conducted to support this.